Vitality in Urban Waterfront Public Spaces: The Case of Laguna, Famagusta - Gaoalafe, Petunia Gomotsang (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This research deals with urban issues and the factors which contribute to the vitality of public spaces, with particular focus on urban waterfront public spaces. Topics dealing with successful public spaces and the revitalisation of waterfront spaces have been explored much by different authors and scholars; however, there is a gap in research that deals specifically with the vitality of waterfront public spaces. Keeping this in mind, the study has its focus on the historically unique waterfront of Famagusta, Laguna Beach, which was once a tourist hotspot but has shown significant decline in its activity since the war broke out in 1974 causing the division of the island and the closure of the Varosha district whose coastline included this waterfront. The question which this research looks to answer is concerned with identifying guidelines which can be implemented to contribute to the vitality of a waterfront space in a conflicted zone such as in the case of the Laguna Beach. This will be based on the general ideology that in order to achieve vitality of the waterfront space, issues concerning accessibility, activity, diversity and security, amongst others, must be taken into account when attempting to alleviate problems. The research methodology is qualitative; specifically case study research method where observation, analytical maps, interviews, and a study of non-governmental organization online platforms are used as means of data collection. This study adds to the body of knowledge on the vitality of Famagusta waterfronts in particular. Keywords: Famagusta, Laguna Beach, Vitality, Urban Waterfront, Public Spaces

ÖZ: Bu araştırma kentsel odaklı olup, liman, kıyı şeridi, sahil gibi kamusal alanların canlandırılması üzerine temellenir. Bu konuda yapılan kaynak taramasında, çeşitli yazar ve bilim insanlarının tarihi kıyı alanlarının yeniden işlevlendirilmesini hedefleyen başarılı örnekleri üzerine odaklandığı gözlemlenmektedir. Diğer kıyı alanlarının canlandırılmasına ilişkin yereterli araştırmanın olmaması, bu araştırmayı özgün kılmaktadır. Bu çerçevede tez, yakın geçmişte önemli bir turizm çekim noktası olan ancak 1974 yılında adada yaşanan savaş ile birlikte, parçası olduğu Maraş kentinin boşaltılması ile önemini ve dolayısı ile çekicliğini yitiren Laguna sahil bölgesini incelemektedir. Bu alanın yeniden canlandırılmasına yönelik kılavuz bilgilerin ne olması gerektiğini irdeleyen araştırma, Laguna sahil bölgesi gibi çatışma sonrası bozulmaya uğrayan kıyı alanlarına odaklanır. Bu anlamda erişilebilirlik, işlev, çeşitlilik ve güvenlik konularını detaylı inceleyen çalışma, bu anahtar kelimeler çerçevesinde öneriler geliştirmeyi hedefler. Gözlem, analitik harita, ve ilgili birey, kurum ve kuruluş ile karşılıklı görüşme gibi niteliksel araştırma yöntemlerini esas alan araştırma, özellikle bu konuda derin araştırmaları olan sivil toplum örgütlerinin birikimlerinden de faydalanmakadır. Çalışma, Laguna sahil bölgesinin yeniden canlandırılmasına ilişkin öneriler sunarken, Mağusa’daki kıyı şeritlerinin canlandırılmasına yönelik bilgi birikimine de katkı koymaktadır. Anahtar Kelimeler: Mağusa, Laguna Sahili, Canlı kentler, Kıyı Alanları, Kamusal Alanlar
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2017. Supervisor: Assist. Prof. Dr. Pınar Uluçay.
Keywords: Architecture; Urban Design Topics; City planning--Environmental aspects--Sustainable development--Waterfronts--Gazimağusa (Cyprus, North); Waterfronts--Land use, Urban--Coastal zone management; Waterfronts--Public spaces; Famagusta; Laguna Beach; Vitality; Urban Waterfront; Public Spaces